(untitled) (Islamic Sciences Journal, 2023)
In the summary of my research, which came under the title “Explanation of a footnote on lamps by Imam Al-Harawi - may God Almighty have mercy on him” (study and investigation). Therefore, this paper sheds light on the personal life of the two imams - may God have mercy on them - and that it starts from their introduction to their most important works and their introduction.